USE OF TECHNOLOGY APPROPRIATE TO BATIK'S SMALL MEDIUM ENTERPRISES UP CLASS THROUGH E-CATALOG - Dodik Jatmika; Mardiana Andarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
The purpose of this study was to find out the effect of using appropriate technology on batik UKM going up the class through e-catalog. The population of this study is the owner and batik maker and business manager of batik in Trenggalek Regency with a total of 107 people, and from all population numbers sampled. The results of the study indicate that the use of appropriate technology influences the E-catalog. The use of appropriate technology has a direct negative effect on UKM in high-grade batik. The e-catalog has an effect on UKM in batik up the class. The use of appropriate technology has an effect on UKM in hand-painted batik going up the class through e-catalog. Recommendations for researchers who will research appropriate technology and e-catalogs for batik are advised to look for implications for the impact on user satisfaction of accounting information systems. Keywords: appropriate technology, UKM go up to class, e-catalog